2012
DOI: 10.2174/092986710793205363
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Relevance of Protein Phosphatase 1 and its Interacting Proteins to Health and Disease

Abstract: Protein phosphorylation is a major regulatory mechanism of signal transduction cascades in eukaryotic cells, catalysed by kinases and reversed by protein phosphatases (PPs). Sequencing of entire genomes has revealed that ~3% of all eukaryotic genes encode kinases or PPs. Surprisingly, there appear to be 2-5 times fewer PPs than kinases. Over the past two decades it has become apparent that the diversity of Ser/Thr-specific PPs (STPP) was achieved not only by the evolution of new catalytic subunits, but also by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…As illustrated by the low TV score for phosphatases (Suppl Table S3), further validation studies are needed before phosphatase inhibition can be pursued as a therapeutic option. Of note, the identity of the PP1/PP2A regulatory subunits mediating Htt dephosphorylation remains unknown, although their inhibition might be more successful than the development of active site inhibitors, since the active phosphatase subunits are very promiscuous in terms of substrate specificity 115 . Upregulation of Akt activity on the other hand could be achieved through the modulation of the upstream IGF-1 and PI3K signalling pathway 107 .…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…As illustrated by the low TV score for phosphatases (Suppl Table S3), further validation studies are needed before phosphatase inhibition can be pursued as a therapeutic option. Of note, the identity of the PP1/PP2A regulatory subunits mediating Htt dephosphorylation remains unknown, although their inhibition might be more successful than the development of active site inhibitors, since the active phosphatase subunits are very promiscuous in terms of substrate specificity 115 . Upregulation of Akt activity on the other hand could be achieved through the modulation of the upstream IGF-1 and PI3K signalling pathway 107 .…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…These regulators mainly include proteins with a degenerate sequence motif ((K/R)X 0 -1 (V/I)p(F/W), known as the RVXF-binding motif to PP1 (9). Biochemical, interaction, and genetic studies clearly indicated that PP1 regulators are as crucial as PP1 itself in the control of cell vitality and survival (10). Hence, the multiple functions of PP1 seem to be organized * This work was supported in part by Inserm, Institut Pasteur de Lille, Université Lille Nord de France, and TGE RMN THC Grant FR-3050, France.…”
mentioning
confidence: 99%
“…In cancer, imbalances in protein phosphorylation systems appear to be an important pathophysiologic mechanism. Since the activation of several kinases results in stimulation of cell signaling pathways that potentiate cell growth and proliferation, it is not surprising that tumor suppressive functions have been attributed to phosphatases (Fardilha et al, 2010).…”
Section: Phosphatases: Essential Regulators Of Cell Signalingmentioning
confidence: 99%
“…Because of the numerous functions of PPP1 and PPP2 catalytic subunits, the long-term usage of these enzyme inhibitors is associated with nephrotoxicity and hepatotoxicity. For this reason, a more satisfactory option seems to be to target PPP1 interacting proteins (PIPs) instead of protein phosphatases directly, as they are more event, tissue, and subcellular compartment specific (Fardilha et al, 2010). Two targeted PPP1-PIP complexes have already been described: (1) the PPP1-GADD34 complex, which is diminished in cells treated with salubrinal-a small molecule that protects the cell from ERstress-induced apoptosis; and (2) PPP1 and histone deacetylases (HDACs), an example of which is trichostatin A, which disrupt the PPP1-HDAC6 complex in glioblastoma and PCa cells (McConnell and Wadzinski, 2009).…”
Section: Ctcs In Metastatic Pcamentioning
confidence: 99%